Международно-правовая регламентация проведения морских научных исследований в водах Мирового океана - Панфилова, Юлия Михайловна; Панфілова, Юлія Михайлівна; Panfilova, Julija (Одеса : Юрид. л-ра, 2012)
The article examines the international legal regulation of Maritime activities of States in the World Ocean, namely the conduct of marine scientific research. Scientific institutions carry out a large volume of scientific-research works practically in all regions of the World Ocean. Given the increasingly important role the ocean plays in the life of mankind as a source of mineral, biological and energy resources, the role of these studies, their relevance and importance to the international community more and more increased.
Панфилова Ю. М. Международно-правовая регламентация проведения морских научных исследований в водах Мирового океана / Ю. М. Панфилова // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 354-361.
Keywords: морское судно; морская деятельность; технические средства; научные исследования; международно-правовые нормы; Мировой океан; морське судно; морська діяльність; технічні засоби; наукові дослідження; міжнародно-правові норми; Світовий океан; ship; Maritime activities; technical resources; scientific research; international legal norms; the World Ocean